Intervention with erythropoietin in sarcopenic patients with femoral intertrochanteric fracture and its potential effects on postoperative rehabilitation - Zhang, Yiou; Chen, Li; Wu, Peng; Lang, Junzhe; Chen, Lei (Geriatrics & gerontology international, 2020)
Aim To explore the intervention with erythropoietin (EPO) in sarcopenic patients with femoral intertrochanteric fractures, and its potential effects on postoperative rehabilitation. Methods A total of 141 patients with femoral intertrochanteric fracture were selected from January 2018 to January 2019. Patients (aged ≥60 years) with indications for EPO use, but without significant medical history, were selected in the present study. All patients were screened for sarcopenia, and divided into the intervention group and control group according to whether they took EPO. The intervention groups received EPO postoperatively every day for 10 days, whereas the control groups received an equal dose of normal saline. Patients' handgrip strength, appendicular skeletal muscle, duration of hospitalization and postoperative infection rate were assessed by analysis. Results Among sarcopenic women, the handgrip strength was higher in the intervention group than in the control group after a week (P < 0.05). However, no significant effect was found in men (P > 0.05). The appendicular skeletal muscle increment of the intervention group with sarcopenia was markedly increased regardless of sex (P < 0.001). In addition, the postoperative infection rate was lower in the intervention group than the control group (P < 0.05), accompanied by a shorter hospital stay due to EPO administration (P < 0.05). Conclusions EPO can improve the muscle strength of female patients with sarcopenia during the perioperative period, and increase muscle mass both of women and men. It can improve the symptoms of sarcopenia, but cannot reverse sarcopenia. Additionally, it can reduce the postoperative complications of patients with hip fracture and shorten the length of hospital stay. Therefore, postoperative administration of EPO might potentially promote rapid postoperative rehabilitation. Geriatr Gerontol Int 2020; 20: 150–155.